Effect of limestone and quartz fillers in UHPC with calcined clay - Hernández Carrillo, Guillermo; Durán Herrera, Alejandro; Tagnit Hamou, Arezki (Multidisciplinary Digital Publishing Institute, 2022)
Ultra-high-performance concrete (UHPC) is a material developed to maximize the engineering characteristics of hydraulic concrete, in terms of durability and mechanical properties, but the adoption of this technology in practice has not turned out as desired, mainly due to the high amounts of cement and silica fume required for its production, and for its consequences on both economic and ecological costs. As an option to improve the impact of UHPC, both on costs and on sustainability, this work evaluates four UHPC series with metakaolin additions of 5%, 10%, 15% and 20%, and the substitution of 37.5% of the Portland cement volume by limestone or quartz filler. The compressive strength, the bulk electrical resistivity and a set of tests for microstructural characterization (TGA, XRD and quantitative EDS) were utilized to better understand the role of calcite on the hydration and pozzolanic reactions in ternary Portland cement-metakaolin-limestone filler. Results indicate that the reaction of calcite is scarce and should be considered as a mere filler, as no increase in AFm phases were found. Nevertheless, the ternary mixture with 15% of metakaolin in addition to cement, and with 37.5% of the Portland cement volume substituted by limestone filler, was the one that presented the best performance in terms of compressive strength and bulk electrical resistivity. The results of the microstructural characterization indicate that the high kaolin content in the metakaolin originated the most significant hydration and pozzolanic reactions development between the ages of 7 and 28 days, as between 28 and 91 the reaction remained dormant. In general, the whole set of results included in this work indicate that limestone filler doesn’t act as a better filler than other kind of powders when used in ternary Portland cement-metakaolin- filler systems.